Four new records of Sipuncula (Annelida) from Northern Brazil - Franco, Letícia C.; Magalhães, Wagner F.; Guimarães, Lívia S.; Oliveira, Deisiane; Rocha, Erika C.; Kawauchi, Gisele Y. (Zootaxa, 2024)
There are very few taxonomic studies of Brazilian sipunculan worms, and the species occurring along the northern coasts are largely understudied. We report herein the occurrence of four shallow water species along the intertidal zones of Bahia and Pernambuco states. Antillesoma antillarum (Grübe & Oersted, 1858) occurs from underneath beach rocks or within sandstone reefs and may reach high densities. The large species Sipunculus (Sipunculus) nudus Linnaeus, 1766, Sipunculus polymyotus Fisher, 1947, and Xenosiphon branchiatus (Fischer, 1895) were collected in sandy-mud, low-energy intertidal environments. For the first time, we report that sipunculans are collected and used as fishing bait by local fishermen in the Western Atlantic. All species are fully described, including notes on their external and internal anatomy.